CiviCRM cookbook : master this web-based constituent relationship management software for nonprofit and civic sector organizations - Horrocks, Tony (Quick answers to common problems., 2013)
This book is written in cookbook style with practical, comprehensive recipes expained with the aid of the necessary screenshots. If you have basic CiviCRM skills and want to further enhance your CiviCRM skills, this book is for you.